MELEK MEDIA DALAM MENGELIMINIR DAMPAK TELEVISI PADA ANAK - Firman Alamsyah Taufik Robbi (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Media literacy will not be balanced, when the broadcast media as producers are not encouraged to become an institution that is